Community knowledges and perception ratings of environmental determinants of the incidences of occurances of unstable malaria in Kericho County,Kenya - Tonui, Warkach K. (International Journal of Scientific Research and Innovative Technology, 2016)
This study was conducted in Kericho County to represent malaria epidemic prone highlands in western Kenya highlands where incidences of unstable (epidemic) malaria burdens have reemerged and on increasing trend and assuming seasonal patterns of occurrences yearly since 1940s and a leading health burden in Kenya in the 21st century. The purpose of the study was to assess communities’ knowledges of the disease and their perception ratings of the listed 39 environmental determinants in questionnaire administered to a sample of 300 household heads purposively chosen from Central Bureau of Statistics estimated at 98678 households in 1999.The respondents were asked to provide information regarding their knowledges of malaria and their perception ratings of significant environmental determinants attributable to the reemergence of occurrences of malaria burdens in their communities.Information obtained was analyzed using Factor Analysis(FA).Majority (75%) of respondents rated malaria as a serious problem in their communities and their knowledges of the disease was based on their own experiences at their household levels and they obtained the information about the disease from radio as the main media. FA classified and ranked in order environmental variables into 3 groups of factors (i) poor accessibility, unaffordability and incorrect use of anti-malarial drugs(ii) social-cultural and household behavioural patterns and(iii) rapid population growth and low Government’s role in management and control of malaria, these accounting for 21.192%,14.083% and 2.924% respectively of the variance in the 39 variables attributable to occurrences of malaria, the first factor accounting for 89% of the variance of all variables. This suggests that malaria knowledges and awareness, subsidy of malaria medication cost by Local and Central Governments, improvements of accessibility to low costs health facilities should be stepped up in the county so that Kenya Government Vision 2030 and beyond Millennium Development Goals can be realized .
Keywords: Community knowledges; Perception Ratings; Environmental Determinants; Unstable Malaria; Burdens; County; Kericho; Kenya